Penerapan Rekayasa Nilai (Value Engineering) Pada Proyek Pembangunan Gedung Kantor Pengadilan Tata Usaha Negara Gorontalo - Nurul Amelia Pulumoduyo; Mohamad Yusuf Tuloli; Arfan Usman Sumaga (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Value Engineering is a method as an effort to save costs by changing the previous design on a particular job with a more economical design in terms of cost but still maintaining the function, quality, and value of a building. In this study, Value Engineering analysis applies six stages, namely the information stage, the function analysis stage, the creative stage, the evaluation stage, the development stage, and the presentation stage. The object of this research project is the Construction of the Gorontalo State Administration Building. The application is carried out on architectural work, namely on wall, floor, and ceiling work. The results of the study showed that there were savings on wall work of Rp. 147,273,333.24 or 6.45% of the initial cost, and on floor work there were savings of Rp. 67.430.567,75 or 6,31% of the initial cost, and on ceiling work there were savings of Rp. 8,124,051.08 or 1.14% of the initial cost. The total savings from all selected work was Rp. 222.840.013,38 or 5,48% of the initial cost of Rp. 4,063,844,279.62